Does Emerging Market Exchange Risk Affect Global Equity Prices? - Carrieri, Francesca; Errunza, Vihang; Majerbi, Basma (Journal of Financial and Quantitative Analysis, 2006)
This paper conducts empirical tests in a conditional setting for 10 developed and 12 emerging markets to determine whether emerging market currency risk is priced and if it spills over into developed market assets. Our empirical model is based on real exchange rate measures and it allows currency risk to compete with broader economic and political risks. We find that emerging market currency risk is priced separately from other local risk factors and that it represents a significant component of equity returns in both developed and emerging markets. We also find that the spillover impact is heightened during emerging market crisis episodes and affects the expected compensation for global risks.